Wana Kerthi as Lived Religion: Ecological Practice and Social Cohesion in Balinese Hinduism - Ervantia Restulita L. Sigai; Suroyo Suroyo; Novena Ade Fredyarini Soedjiwo; Bima Maulana Putra; Saida Kheira Benammar; Joachim Baaden (Jurnal Studi Agama dan Masyarakat, 2026)
Environmental degradation, biodiversity loss, and climate change have become urgent global challenges, prompting renewed attention to the role of cultural and religious frameworks in shaping sustainable human–nature relationships. The study examined Wana Kerthi, a Balinese Hindu principle of forest preservation, as an indigenous eco-theology integrating religious devotion, environmental ethics, and social solidarity. Drawing on qualitative methods, including in-depth interviews, participant observation, and document analysis in selected Balinese communities, the particular study explored how Wana Kerthi is understood and practiced within everyday religious and social life. The findings found out that Wana Kerthi functions not only as a theological concept but also as a lived moral system in which forests are regarded as sacred entities and ecological care is expressed as an act of devotion (bhakti). At the same time, communal practices such as rituals, ngayah, and customary law (awig-awig) reinforce social cohesion and collective responsibility for environmental stewardship. Moreover, this study contributed to the growing discourse on religion and ecology by demonstrating how local belief systems serve as practical frameworks for sustainability. It offers a synthesis between Eco-theological and sociological perspectives, positioning Wana Kerthi as a model of moral ecology. Therefore, the findings provide insights for global discussions on community-based environmental governance rooted in spiritual values.